Republic of Mozambique : First Review Under the Policy Support Instrument; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report ;, 2008)
The strong macroeconomic performance and the implementation of prudent fiscal and monetary policies and a flexible exchange rate regime have helped Mozambique to perform well under the Policy Support Instrument (PSI). Executive Directors advised to maintain macroeconomic stability and accelerate structural reforms to sustain rapid growth. Directors stressed the need for fiscal transparency and adopting regulations to the Mining and Petroleum Fiscal Regime laws. Directors appreciated the principles of the Extractive Industries Transparency Initiative, welcomed its monetary policy stance, and encouraged authorities to embark on revenue efforts to achieve the MDGs.